A focused issue on identifying, building, and linking competences - Sanchez, Ron; Heene, Aimé (Emerald, 2010)
The papers in this volume explore key challenges in identifying, building, and linking competences within and between organizations. The first paper describes a facilitated process through managers may identify an organization's current competences and assess which of its capabilities may constitute the "core" of its distinctive competences. Subsequent papers elaborate basic issues in building organizational competence, including balancing the exploration of new competences and the exploitation of current competences, creating strategic options through competence building, linking the capabilities of alliance partners to target and build new competences, using product architectures in building and maintaining competences, the recursive nature of competence building processes, and the nature and role of management processes in competence building. A final paper analyzes the intellectual structure of and influences within the competence-based management perspective.
Description based on print version record.
Keywords: Organizational effectiveness.; Organizational learning.; Core competencies.; Management of specific areas.; Personnel & human resources management.; Business & Economics -- Management science.; Business & Economics -- Organizational Behavior.; Business & Economics -- Human Resources & Personnel Management.; elektronické knihy; electronic books